Tang Tri-Color Glazed Ceramics: Wisdom and Inheritance of Luoyang city, China - Yang, Mengmin; Sriruksa, Arunee; Sriruksa, Kittisan (Technium Social Sciences Journal, 2024)
This article aims to study the wisdom and inheritance of Tang tri-color glazed ceramics in Nanshishan Village, Luoyang using qualitative research methods to survey, interview, observation, and focus group discussions on the inheritors and heirs of Gao's large-scale factory and Wang's family shop in Nanshishan Village. The structural functionalism theory were applied in analyzing the wisdom in history, current situation, and wisdom of Tang tri-color glazed ceramics in Nanshishan, Luoyang, consisting of production steps of large-scale factory and local family shops. The 5W communication theory was used to study the inheritors, heirs, inheritance content, inheritance methods, and inheritance effects of Tang tri-color glazed ceramics, providing reference for better inheritance of local family shops in Nanshishan Village.